The effects of behavior‐specific praise and public posting in secondary classrooms. Issue 7 (21st April 2020) - O'Handley, Roderick D.; Olmi, D. Joe; Dufrene, Brad A.; Tingstrom, Daniel H.; Whipple, Heather
Abstract: Behavior‐specific praise (BSP) and other forms of positive feedback and public acknowledgment are underutilized in secondary classrooms. Surprisingly, few studies have evaluated the independent effects of BSP in these settings. Using a multiple baseline design with an embedded A/B/B + C condition sequence, the purpose of the current study was to evaluate the effects of BSP and BSP combined with public posting on the appropriately engaged and disruptive behaviors across 4 secondary classrooms. Results supported a functional relation between BSP alone and improvements in students' appropriately engaged and disruptive behaviors. Combining BSP with public posting, which involved writing students' names on the classroom whiteboard, further increased students' appropriately engaged behaviors but had mixed effects on students' disruptive behaviors. Practical implications, limitations, and directions for future research are discussed.